5.91%-efficient Sb2Se3 solar cells with a radio-frequency magnetron-sputtered CdS buffer layer. (September 2019) - Hu, Xiaobo; Tao, Jiahua; Wang, Youyang; Xue, Juanjuan; Weng, Guoen; Zhang, Chuanjun; Chen, Shaoqiang; Zhu, Ziqiang; Chu, Junhao
Graphical abstract: Highlights: 5.91%-efficient Sb2 Se3 solar cells was achieved with sputtered CdS buffer layer. The highest efficiency was achieved with CdS thickness of 90 nm. The optimal cell owns the optimal grain orientation and the best morphology. The optimal cell owns the lowest carrier recombination rates at all regions. Abstract: Superstrate ITO/CdS/Sb2 Se3 /Au thin-film solar cells were fabricated with a CdS film produced by a radio-frequency (RF) magnetron-sputtering method as the buffer layer. The effect of the CdS layer thickness (70–120 nm) on the properties of Sb2 Se3 thin films and the performance of the solar cells was investigated. The optimal CdS thickness was 90 nm, which led to the best power conversion efficiency of 5.91%; to the best of our knowledge, this is the highest efficiency for Sb2 Se3 solar cells with a sputtered CdS buffer layer to date. X-ray diffraction and scanning electron microscope results indicated that the Sb2 Se3 films grown on 90-nm-thick CdS layers had the optimal grain orientation and the best morphology. The current–voltage ( J–V ) and admittance results indicated that the Sb2 Se3 cell with a 90-nm-thick CdS layer had the lowest saturation current and the smallest defect densities. Moreover, temperature- and light intensity-dependent open-circuit ( V oc ) measurements revealed that the carrier recombination rates at the CdS/Sb2 Se3 interface, space-charge region (SCR), and quasi-neutral region (QNR) all achieved the smallest value for the Sb2 Se3 cells with a 90-nm CdS buffer layer. These data account for the optimal cell performance and offer new research directions for solving challenges of chemical bath deposition of CdS in Sb2 Se3 solar cells.